2011
DOI: 10.1103/physrevb.83.245324
|View full text |Cite
|
Sign up to set email alerts
|

Tuning of the spin-orbit interaction in a quantum dot by an in-plane magnetic field

Abstract: Using an exact diagonalization approach we show that one-and two-electron InAs quantum dots exhibit avoided crossing in the energy spectra that are induced by the spin-orbit coupling in the presence of an in-plane external magnetic field. The width of the avoided crossings depends strongly on the orientation of the magnetic field which reveals the intrinsic anisotropy of the spin-orbit coupling interactions. We find that for specific orientations of the magnetic field avoided crossings vanish. Value of this or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 48 publications
6
36
0
Order By: Relevance
“…27 It manifests itself in spin relaxation, 28,29 level anticrossings in InAs single and double dots, 30,31 and in the electric dipole spin resonance (EDSR), 32,33 both in GaAs 34,35 and InAs 36 double dots. It is important to emphasize the existence of different mechanisms that couple the electron spin to the orbital degrees of freedom.…”
Section: Electron-and Nuclear-spin Dynamicsmentioning
confidence: 99%
“…27 It manifests itself in spin relaxation, 28,29 level anticrossings in InAs single and double dots, 30,31 and in the electric dipole spin resonance (EDSR), 32,33 both in GaAs 34,35 and InAs 36 double dots. It is important to emphasize the existence of different mechanisms that couple the electron spin to the orbital degrees of freedom.…”
Section: Electron-and Nuclear-spin Dynamicsmentioning
confidence: 99%
“…This is qualitatively the same behavior found by Nowak et al [145], thus confirming the validity of their simplified cuboidal model in explaining the origin of the offset.…”
Section: Angular Dependence Of the Soisupporting
confidence: 78%
“…In the same publication it was suggested that the origin of this offset might be a consequence of the QD elongated pyramidal geometry along with the contribution of only RSOI. Subsequently, a theoretical study by Nowak et al [145] proposed an alternative origin. They attributed the offset to the combined action of both RSOI and DSOI in elongated QDs, and not solely to RSOI.…”
Section: Control Of Electron Spin-orbit Anisotropy In Pyramidal Qdsmentioning
confidence: 99%
“…The eigenspinors | (16) in order to take part in the minimization procedure and in the determination of λ. However, this approach will obviously give rise to some complications in the energy expression used in the calculation of λ without giving any appreciable change in its value.…”
Section: O-center Impuritymentioning
confidence: 99%
“…The previous studies are concerned with three types of spinorbit interactions namely, Rashba [118], Dresselhaus [4,11,12,14,16,19,20] and conventional interactions [2125]. The study of Rashba and Dresselhaus interactions have been mainly considered in two--dimensional geometries.…”
Section: Introductionmentioning
confidence: 99%